Epigenetic Regulation of Non-Lymphoid Cells by Bisphenol A, a Model Endocrine Disrupter: Potential Implications for Immunoregulation - Khan, Deena; Ahmed, S. Ansar (Frontiers in Endocrinology, 2015)
Endocrine disrupting chemicals (EDC) abound in the environment since many compounds are released from chemical, agricultural, pharmaceutical and consumer product industries. Many of the EDCs such as Bisphenol A (BPA) have estrogenic activity or interfere with endogenous sex hormones. Experimental studies have reported a positive correlation of BPA with reproductive toxicity, altered growth and immune dysregulation. Although the precise relevance of these studies to the environmental levels is unclear, nevertheless, their potential health implications remain a concern. One possible mechanism by which BPA can alter genes is by regulating epigenetics, including microRNA, alteration of methylation and histone acetylation. There is now wealth of information on BPA effects on non-lymphoid cells and by comparison, paucity of data on effects of BPA on the immune system. In this mini review, we will highlight BPA regulation of estrogen receptor-mediated immune cell functions and in different inflammatory conditions. In addition, BPA-mediated epigenetic regulation of non-lymphoid cells is emphasized. We recognize that most of these studies are on non-lymphoid cells, and given that BPA also affects the immune system, it is plausible that BPA could have similar epigenetic regulation in immune cells. It is hoped that this review will stimulate studies in this area to ascertain whether or not BPA epigenetically regulates the cells of the immune system.